Solar thermochemical processes for autonomous cooling production - (:unkn) unknown (My University, 2024)
Cold production is a major energy and health issue for many African regions, particularly for the preservation of food and heat-sensitive products. Current technologies rely mainly on electrical compressor, requiring them to be grid connected. This can be problematic in some rural areas of Africa, often isolated and disconnected from power grids. The development of simple, autonomous refrigeration or ice-making technologies that make use of solar energy is a relevant solution to these major issues. The use of solar energy in its photovoltaic form in conventional compression refrigeration technologies is penalized by its reliability and often questioned environmental impact. Sorption-based processes, which have the advantage of using only solar energy in thermal form, such as thermochemical processes involving a reversible chemical sorption between a gas and a reactive salt, could be a promising alternative to these conventional refrigeration systems due to their simplicity and reliability. Such processes use only solar thermal energy to heat a reactor, enabling chemical decomposition of the reactive salt, which desorbs a gas which condenses at ambient temperature in a condenser where it accumulates in liquid state. During the night, the reactor naturally cools down to ambient temperature and chemically reabsorbs the refrigerant gas, which evaporates in the evaporator, producing the desired cold at temperatures as low as -15°C. Operation of such a passive process has the advantage of being totally silent, robust since it has no moving parts, autonomous and without active control. Such sorption-based solar cooling processes could be used relevantly to develop stand-alone cold shelters for preserving agricultural produce or to produce ice for preserving fishery or agro-pastoral products, with a daily cooling capacity ranging from 900 to 1200Wh/m² or a daily ice production of 7 to 10 kg/m² of solar collector.</
Keywords: African Research